Turkish EFL Teachers’ Self-efficacy Levels in the Implementation of Self-Regulated Learning - Akyıldız, Seçil Tümen; Kaya, Vildan Donmuş (Disiplinlerarası Eğitim ve Araştırma Derneği, 2023)
Despite the availability of resources and efforts, English as a foreign language (EFL) learners and EFL teachers face challenges in achieving proficiency in the target language in Turkey. Self-regulation, a cognitive and motivational trait, is crucial in foreign language learning. Self-regulated learning (SRL) focuses on learners taking responsibility for their entire learning process, enabling them to engage in metacognitive processes. It has gained significant attention in recent years due to the rise of autonomous learning practices and the importance of management skills in EFL education. Teachers can enhance their awareness and oversight of their students' progress towards their objectives through the use of metacognitive skills. However, there is a lack of focus on teachers' self-efficacy levels in adopting SRL in language education. This research aimed to investigate if Turkish EFL teachers actively encourage SRL in their instruction, focusing on their roles in implementing SRL theory. The causal-comparative model was utilized in the course of this study. A sample of 211 EFL instructors from high schools in an eastern city in Turkey, was investigated. An instrument titled "Teacher Self-Efficacy for Implementing Self-Regulated Learning" was utilized to gather the data. Descriptive statistics, independent sample t-test, and one-way ANOVA analysis were used to analyze the research data. Findings suggested that the average level of self-efficacy among Turkish EFL teachers in utilizing SRL strategies to engage students is moderate. The results of the study are of great implications for the role of educators in promoting students' autonomy and lifelong learning.

Kaynak ve çabaların mevcudiyetine rağmen, İngilizceyi yabancı dil olarak öğrenenler ve İngilizce öğretmenleri Türkiye'de hedef dilde yeterlilik kazanmada zorluklarla karşılaşmaktadır. Bilişsel ve motivasyonel bir özellik olan öz düzenleme, yabancı dil öğreniminde çok önemlidir. Öz düzenlemeli öğrenme (SRL), öğrencilerin tüm öğrenme süreçlerinin sorumluluğunu üstlenmelerine odaklanarak, meta-bilişsel süreçlere katılmalarını sağlar. Son yıllarda özerk öğrenme uygulamalarının yükselişi ve EFL eğitiminde yönetim becerilerinin önemi nedeniyle önemli ölçüde ilgi görmüştür. Öğretmenler, meta-bilişsel becerilerin kullanımı yoluyla öğrencilerinin hedeflerine doğru ilerlemeleri konusunda farkındalıklarını ve denetimlerini artırabilirler. SRL, son yıllarda özerk öğrenme uygulamalarının yükselişi ve EFL eğitiminde yönetim becerilerinin önemi nedeniyle önemli ölçüde ilgi görmüştür. Ancak, öğretmenlerin dil eğitiminde SRL'yi benimsemedeki öz yeterlilik düzeylerine odaklanılmamıştır. Bu araştırma, Türk EFL öğretmenlerinin, SRL teorisini uygulamadaki rollerine odaklanarak, öğretimlerinde SRL'yi aktif olarak teşvik edip etmediklerini araştırmayı amaçlamıştır. Çalışmada, Türk EFL öğretmenlerinin EFL'de SRL'yi uygulamada öz yeterlilik düzeylerine ilişkin bulgular sunuldu ve kapsamlı bir tartışma yürütüldü.
Turkish EFL Teachers’ Self Efficacy Levels in the Implementation of Self-Regulated Learning / Türk EFL Öğretmenlerinin Öz-Düzenlemeli Öğrenmenin Uygulanmasında Öz Yeterlik Düzeyleri
Keywords: Educational Psychology; Eğitim Psikolojisi